MAIN NOTIONS OF AXIOLOGICAL LINGUISTICS - Abdug'affarova Gulhayo Abdug'affar qizi (Western European Studies, 2025)
Axiological linguistic is one of the relatively new areas of linguistics, studies the value, meaning and moral aspects of language. In this direction analyzes the relationship between the cultural, moral and social significance, language and values, as well as language and human moral principles. Axiological linguistics is related to the philosophical, cultural and social contexts of language and linguistics, focuses on the functions of language. This article will consider the main concepts axiological linguistics, its scientific significance and practical application
Keywords: Axiology; Axiological Linguistics; Values